Direct fabrication of bio-inspired gecko-like geometries with vat polymerization additive manufacturing method. (8th May 2018) - Davoudinejad, A; Ribo, M M; Pedersen, D B; Islam, A; Tosello, G
Abstract: Functional surfaces have proven their potential to solve many engineering problems, attracting great interest among the scientific community. Bio-inspired multi-hierarchical micro-structures grant the surfaces with new properties, such as hydrophobicity, adhesion, unique optical properties and so on. The geometry and fabrication of these surfaces are still under research. In this study, the feasibility of using direct fabrication of microscale features by additive manufacturing (AM) processes was investigated. The investigation was carried out using a specifically designed vat photopolymerization AM machine-tool suitable for precision manufacturing at the micro dimensional scale which has previously been developed, built and validated at the Technical University of Denmark. It was shown that it was possible to replicate a simplified surface inspired by the Tokay gecko, the geometry was previously designed and replicated by a complex multi-step micromanufacturing method extracted from the literature and used as benchmark. Ultimately, the smallest printed features were analyzed by conducting a sensitivity analysis to obtain the righteous parameters in terms of layer thickness and exposure time. Moreover, two more intricate designs were fabricated with the same parameters to assess the surfaces functionality by its wettability. The surface with increased density and decreased feature size showed a water contact angle (CA) of 124° ± 0.10°, agreeing with the Cassie–Baxter model. These results indicate the possibility of using precision AM for a rapid, easy and reliable fabrication method for functional surfaces.